2021
DOI: 10.1155/2021/8493431
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00662 Exerts an Oncogenic Effect on Osteosarcoma by the miR-16-5p/ITPR1 Axis

Abstract: Background. Osteosarcoma (OS) is one of the most malignant bone tumors and has a high metastatic rate. Increasing research has demonstrated the vital roles of long noncoding RNAs (lncRNAs) in human cancers, including OS. LncRNA LINC00662 has been revealed to act as an oncogene involved in multiple tumor progression. This study aimed to investigate the expression pattern, function, and regulatory mechanism of LINC00662 in OS. Methods. Patients who underwent OS surgery were involved in this study. Experiments in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 32 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…The remaining 32 studies were then carefully reviewed by reading the full article. Of them, 9 were eliminated due to the lack of eligible data, 9 were eliminated since they were physical experimental studies, and 14 studies ( Gong et al, 2018 ; Li et al, 2019 ; Wang et al, 2019 ; Cheng B. et al, 2020 ; Cheng L. et al, 2020 ; Guo et al, 2020 ; Liu and Meng, 2020 ; Tian et al, 2020 ; Wei et al, 2020 ; Zhang et al, 2020 ; Ma et al, 2021 ; Wu et al, 2021 ; Yu et al, 2021 ; Wang et al, 2022 ) were finally included for meta-analysis. The study screening procedure is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining 32 studies were then carefully reviewed by reading the full article. Of them, 9 were eliminated due to the lack of eligible data, 9 were eliminated since they were physical experimental studies, and 14 studies ( Gong et al, 2018 ; Li et al, 2019 ; Wang et al, 2019 ; Cheng B. et al, 2020 ; Cheng L. et al, 2020 ; Guo et al, 2020 ; Liu and Meng, 2020 ; Tian et al, 2020 ; Wei et al, 2020 ; Zhang et al, 2020 ; Ma et al, 2021 ; Wu et al, 2021 ; Yu et al, 2021 ; Wang et al, 2022 ) were finally included for meta-analysis. The study screening procedure is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All of these articles were conducted in China and published between 2018 and 2022. The above articles included ten tumors, including three cases of OSA ( Liu and Meng, 2020 ; Yu et al, 2021 ; Wang et al, 2022 ), two cases of HCC ( Guo et al, 2020 ; Tian et al, 2020 ), two cases of CRC ( Wang et al, 2019 ; Cheng B. et al, 2020 ), one case of bladder cancer ( Ma et al, 2021 ), one case of lung cancer ( Gong et al, 2018 ), one case of CC ( Wei et al, 2020 ), one case of ESCC ( Zhang et al, 2020 ), one case of BC ( Cheng L. et al, 2020 ), one case of PCa ( Li et al, 2019 ), and one case of OC ( Wu et al, 2021 ). Nine of these articles ( Gong et al, 2018 ; Li et al, 2019 ; Wang et al, 2019 ; Cheng B. et al, 2020 ; Guo et al, 2020 ; Tian et al, 2020 ; Ma et al, 2021 ; Wu et al, 2021 ; Yu et al, 2021 ) reported OS, two ( Guo et al, 2020 ; Tian et al, 2020 ) reported RFS, and all studies reported clinical parameters.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations